Loyalty in the supermarket - Vieira, Valter A. (2007)
Loyalty has been a hot topic in marketing management, not only for academics, but also for managers. In that sense, the main goal of this paper is to identify the variables that discriminate loyalty groups. Therefore, seven hypotheses have been proposed which might have an impact on loyalty groups. Based on discriminant analysis, the paper analyzes and discusses the data, and presents a conclusion that the more important variables on loyalty in the supermarket are affective commitment, satisfaction with its environment and value provided by supermarket experiences. Moreover, the results also indicated that the theoretical model achieved a variance in the loyalty construct of canonical R-squared = 0.78. It could be considered a good value to the final model. Final considerations and study limitations conclude the paper.